Islam and Freedom of Belief: The Challenge of Female Apostasy - Khalfaoui, Mouez (Hawwa, 2025)
Taking into consideration the significance of the debate about apostasy and, especially, female apostasy with regard to its direct correlation to international relations, human rights norms and the development of Islamic law in modern societies, this study addresses the following questions. How has female apostasy been debated by scholars of Islamic law? Why did scholars of the Ḥanafi school, the most geographically widespread school of Islamic law, distinguish between genders with regard to the punishment for apostasy? How could this debate be used in contemporary discussions about apostasy? These questions will be debated successively.